Coordination Costs and Homelessness Housing Form Choice - Edmund Poku Adu; Julius A. Nukpezah (Public Administration Review, 2026)
ABSTRACT Local implementers have discretion in selecting forms of housing for the homeless, yet the determinants of these choices remain poorly understood. Using the institutional collective action (ICA) framework, this study examines California's Homekey program to assess how coordination demands shape decisions among hotel conversions, multifamily acquisitions, and modular or new construction. Drawing on binary logistic, generalized estimating equation (GEE), and multinomial logistic models, we find that larger projects and those designated as permanent housing are significantly more likely to pursue hotel conversions. Housing authorities—owing to their specialized missions and lower form‐specific coordination costs—are over six times more likely than cities to select multifamily acquisition. Local vacancy constraints further steer implementers away from modular or new construction and toward hotel conversions. These results demonstrate that implementation form is not a neutral technical decision but an institutional response to coordination challenges embedded in intergovernmental and interorganizational contexts.